Transmissão de calor em sistemas nanoscópicos - Tavares, Thiago Romeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The interest in the study of the transmission of mechanical vibrations in nanoscale systems, such as carbon nanotubes, graphene or similar structures, is driven by the technological importance attributed to the understanding of physical phenomena in this type of system. Understanding the behavior of heat and vibrations at the nanoscale may be important to the operation of devices that will be developed in the near future for nanoelectronics. During the development of the present work, we study the mechanisms of heat transfer with the aid of completely atomistic computational models. In particular, we intend to describe the heat transmission in different directions in nanodevices. For this study, the interactions between the atoms will be described with Tersoff potential. Furthermore, the main atomistic simulation tool used in this work is the well known LAMMPS software. It will also be evaluated the possibility of varying the behavior of the heat transmission coefficient through changes in the geometry of the considered devices, such as deformations or different arrangements of defects, for example

O interesse pelo estudo da transmissão de vibrações mecânicas em sistemas nanoscópicos, como nanotubos de carbono, grafeno ou estruturas similares, é motivado pela importância tecnológica, que existe atualmente, da compreensão dos fenômenos físicos neste tipo de sistema. Entender o comportamento do calor e das vibrações em sistemas na escala nanoscópica pode ter importância para a compreensão, também, do funcionamento de dispositivos desenvolvidos para a nanoeletrônica. Durante o desenvolvimento deste trabalho, serão estudados os mecanismos de transmissão de calor em sistemas descritos com o auxílio de modelos computacionais atomísticos. Em particular, pretendemos descrever a transmissão de calor em direções diferentes em nanodispositivos. Para este estudo, as interações entre os átomos considerados serão descritas principalmente com o potencial Tersoff. Além disso, serão utilizadas diversas ferramentas de simulação atomística, como o software LAMMPS. Será também avaliada a possibilidade de variar o comportamento do calor transmitido em dispositivos por meio de mudanças na geometria, como ocorre quando o sistema sofre uma deformação, por exemplo
Keywords: Física; Calor - Transmissão; Grafeno